A Facile Oxidative Opening of the C-Ring in Luotonin A and Derivatives - Amra Ibric; Kathrin Dutter; Brigitte Marian; Norbert Haider (Molecules, 2017)
An oxidative ring opening reaction of the central ring C in the alkaloid Luotonin A and two of its derivatives was found to occur upon heating with an excess amine and potassium carbonate in dimethylsulfoxide (DMSO) solution in the presence of air oxygen. The structure of the novel amide-type products was elucidated and a possible mechanism for this reaction is proposed. Four of the new compounds show moderate in vitro anticancer activity towards human colon adenocarcinoma cells.